Vegetation Analysis of Sapling and Understorey Invaded by Invasive Alien Species (IAS) Bellucia pentamera Naudin in Lembah Harau Sanctuary - Solfiyeni; Hafizhah Rahmayani; Winda Gusmawarni (JURNAL SAINS NATURAL, 2023)
Bellucia pentamera Naudin, the proliferation across Indonesia, notably in Sumatra, has the potential to lessen biodiversity there. On the other hand, little is known about the effects of its invasion on plants and the ecology. The objective of this study was to evaluate the genetic makeup and structural characteristics of saplings and the understorey vegetation in the B. pentamera-infested Lembah Harau sanctuary forest zone. Vegetation analysis was conducted in the sanctuary Lembah harau forest with two levels of dominance: Station 1 was lightly invaded by B. pentamera, and Station 2 was heavily invaded by B. pentamera. Purposive sampling is used in the plot method. The findings found that the number of sapling species at stations 1 and 2 was 18 and seven, respectively. Station 1 had 38 species of understorey, while station 2 had 26. The Melastomataceae family dominated the sapling strata and understorey at stations 1 and 2. The B. pentamera species has the highest Important Value Index sapling at Stations 1 and 2. While in the understorey, station 1 has the highest Importance Value Index (24.45%) and the highest B. pentamera species (59.10%). Both stations have a moderate Diversity Index (H') for sapling and understorey levels. The Community Similarity Index (IS) of sapling and plant levels at stations 1 and 2 is relatively low.